By-Clime: Development of PBL-SSI-based e-module on climate change to enhance SA and ITS of upper secondary students - Ayu Dayang Lestari; Hadi Suwono; Sitoresmi Prabaningtyas (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Climate change presents complex challenges for science education, demanding innovative digital resources that connect scientific understanding with real-world environmental problems. This study aimed to develop and validate By-Clime, an e-module based on the Problem-Based Learning and Socioscientific Issues (PBL-SSI) framework, designed to facilitate students’ learning on climate change topics while promoting sustainability-oriented thinking. The e-module integrates content on climate phenomena, impacts, and mitigation strategies through contextual problem scenarios, enabling students to connect scientific concepts with authentic socio-environmental contexts and apply cross-disciplinary reasoning. The development process followed the Lee and Owens instructional design model, which includes stages of analysis, design, development, implementation, and evaluation. The results showed that media experts rated the module at 89.5%, categorized as highly valid in feasibility, visual design, and integration. Material experts provided perfect scores of 100% for content relevance, feasibility, and language clarity. Practitioner evaluation also yielded a high validity score of 98.1%, particularly in presentation, material support, and completeness. These findings confirm that By-Clime is a feasible, relevant, and pedagogically sound learning resource for climate change education, fostering students’ sustainability awareness (SA) and interdisciplinary thinking skills (ITS).